An effective range estimation and state-of-charge to mitigate range anxiety in electric vehicles - Shana Lakshmi Prasad; Abhishek Gudipalli (Heliyon, 2025)
This article presents a performance investigation of the range and state of electric charge vehicles based on different drive cycles and analyzed. Range anxiety is the major concern in electric vehicles globally. To mitigate the range anxiety issue by reducing the energy consumption in electric vehicles further reduces the range-related problem, and the state of charge reduces the demand for driver's power. The drive cycles predict, optimize, and simulate the performance range of Ev's real-world driving conditions. This research thoroughly focuses on the performance range of electric vehicles incorporated with the state of charge based on various standard drive cycles. A drive cycle plays a vital role in estimating energy consumption (EC) per km. There are many standard drive cycles World Wide Harmonized Light Vehicles Test Procedure (WLTP Class-3), the New European Drive Cycle (NEDC), the Modified Indian Drive Cycle (MIDC), the Indian Drive Cycle (IDC) used to investigate and evaluate Electric vehicle (EVs) performance range and state of charge (SoC). Range obtained from above drive WLTP Class-3, NEDC, MIDC, and IDC drive cycles 135.1123.8115.7 and 101.5 km, respectively. Due to improved road conditions, the WLTP Class-3 drive cycle offers more than the others. Due to road conditions, the IDC drive cycle offers a shorter range of 101.5 km.